2022
DOI: 10.1080/13880209.2022.2089691
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterisation and complement fixation activity of acidic polysaccharides from Argemone mexicana used as antimalarials in Mali

Abstract: Context Global studies on Argemone mexicana L. (Papaveraceae) traditionally used against malaria in Mali are limited to its low-mass compounds activities, and little information on its bioactive polysaccharides is available. Objective This study determines the structure and the immunomodulatory activity of polysaccharides from aerial parts of A. mexicana . Materials and methods Acidic poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
2
0
0
Order By: Relevance
“…It was noticed that the first SEC fractions showed the highest complement fixation activity, and they are mainly composed of T‐, 1,5‐ and 1,3,5‐linked Ara f , and/or T‐, 1,3‐ and 1,3,6‐linked Gal p in addition to a HG linear chain. This is consistent with previous conclusions for pectic polysaccharides from various medicinal plants, that arabinans and AG‐II moieties are important to attach to human complement 43‐45 . Earlier studies also concluded that pectic polysaccharides with higher Mw had much more potent complement fixation activity, 46 which matched with our primary finding that the second SEC fractions with lower Mw (41.6–105 kDa) were shown to be inactive (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It was noticed that the first SEC fractions showed the highest complement fixation activity, and they are mainly composed of T‐, 1,5‐ and 1,3,5‐linked Ara f , and/or T‐, 1,3‐ and 1,3,6‐linked Gal p in addition to a HG linear chain. This is consistent with previous conclusions for pectic polysaccharides from various medicinal plants, that arabinans and AG‐II moieties are important to attach to human complement 43‐45 . Earlier studies also concluded that pectic polysaccharides with higher Mw had much more potent complement fixation activity, 46 which matched with our primary finding that the second SEC fractions with lower Mw (41.6–105 kDa) were shown to be inactive (Fig.…”
Section: Resultssupporting
confidence: 93%
“…This is consistent with previous conclusions for pectic polysaccharides from various medicinal plants, that arabinans and AG-II moieties are important to attach to human complement. [43][44][45] Earlier studies also concluded that pectic polysaccharides with higher Mw had much more potent complement fixation activity, 46 which matched with our primary finding that the second SEC fractions with lower Mw (41.6-105 kDa) were shown to be inactive (Fig. 5).…”
Section: Complement-fixating Activity Of Polysaccharides Isolated Fro...supporting
confidence: 88%